Strata, tęsknota, ciekawość - Sośnicki, Dariusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-US">In his piece, the author of the article ponders on the experience of loss in human life. It is this particular experience, as well as the accompanying longing, that form the basic components of an elegiac attitude. However, in its broader sense, loss becomes one of the most universal experiences in literature and the arts of the twentieth century. After all, they shared the conviction that reality, no matter how looked upon, was never fully accessible to us and that man always played a losing game with it. Contrary to outward appearances, the above also applies to the creators of avant-garde movements. An analysis of the poem Do NN***, written by Miron Białoszewski, carried out first within the context of elegy and then with reference to the techniques and the program of cubism, makes us aware that Białoszewski somehow evades both elegiac mood and the avant-garde principles such as they are underlined in its program. The driving force for his writing is then curiosity. And it is curiosity, and just curiosity, independent and one that cannot be reduced to just the desire to know, that forms the only real alternative that, in a way, always remains metaphysical.